Analysis of the impact of Arabic-Malay bilingual dictionaries in Malaysia - Dollah, Nafi@Hanafi; Salisu, Alfa Muhammed; Abdullah, Nurazzelena (CASIS, Universiti Teknologi Malaysia, 2015)
The emergence of Arabic language and Islamic religion in the Malay Archipelago which comprises the present day Malaysia, Singapore, Indonesia, Brunei Darussalam, part of the Philippines as well as southern Thailand gave birth to Islamic education through the medium of Arabic language. This was inevitable because of the mutual relationship between Arabic language and Islam. To have better understanding of the Quran as the primary source of Islam is to have mastery of Arabic language. Hence the Muslim scholars in the Malay Archipelago resorted to the writing of Arabic Malay dictionaries which could help in the proper understanding of Arabic texts such as the Quran and Hadith which were primarily in Arabic language. This effort continues from generation to another until modern times which gave rise to the production of different types of Arabic Malay bilingual dictionaries. Some of these dictionaries have contributed to the general education of the Malays for their precision in translation. This study however, is an attempt to examine and analyse the contributions of selected Malay Arabic dictionaries to the Malay world in order to determine their precision in translation from Arabic to Malay language with reference to their methodologies with the aim of suggesting standards by which an ideal and all-encompassing Arabic Malay bilingual dictionary could emerge. Keywords: Analysis, Impact, Arabic-Malay, Bilingual Dictionaries, Archipelago.